skills and its relationship to the with concept of self in social The chidren kindergarten age (4-6) years (Journal Of Educational and Psychological Researches, 2013)
The interest in Multi social skills and self-concept is extremely  important for many of the scholars of education and psychology has taken a great deal in their writings and their interests as they see that social skills training is to make sure of the same, and that whenever enable the individual from acquiring social skills whenever asserted itself.The research aims know social skills and self-concept and their relationship to the children Riyadh age (4-6 years), and the research sample consisted of(200) boys and girls from kindergarten in the city of Baghdad Bjanbey Rusafa second and Karkh second.And to the objectives of the research realized the researcher has built two measures of social skills and self-concept, after informed on the literature and previous studies, and included a measure of social skills (72) and paragraph measure of self-concept (108) as the final drafted paragraphThe researcher also made of standard characteristics of the two scales of truth and stability was verified honesty in two ways honesty and sincerity of virtual construction, was the extraction of consistency in two ways and retest Cronbach Alfa The search found the following results:1- Riyadh children enjoy social skills.2 - There are no statistically significant differences between children in social skills, according to a variable (sex).3 - There are no statistically significant differences between children in social skills, according to a variable (age).4 - Riyadh children enjoy the concept of self-5 - There are no statistically significant differences between children in social skills, according to a variable (sex).6 -There are no statistically significant differences between children in social skills, according to a variable (age). 7 - There is a positive correlation between social skills and self-concept.The researcher also put some of the recommendations and proposals.